2012
DOI: 10.1183/09031936.00075612
|View full text |Cite
|
Sign up to set email alerts
|

Barrier responses of human bronchial epithelial cells to grass pollen exposure

Abstract: The airway epithelium forms a physical, chemical and immunological barrier against inhaled environmental substances. In asthma, these barrier properties are thought to be abnormal. In this study, we analysed the effect of grass pollen on the physical and immunological barrier properties of differentiated human primary bronchial epithelial cells.Following exposure to Timothy grass (Phleum pratense) pollen extract, the integrity of the physical barrier was not impaired as monitored by measuring the transepitheli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
52
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 37 publications
0
52
0
Order By: Relevance
“…Epithelial cells actively secrete immune mediators in response to environmental stimuli [61], which are different in patients with asthma compared with controls [62]. Asthmatic epithelium also has altered barrier function [63], and is a critical bridge between external environmental exposures and pulmonary inflammatory and immune responses [64]. Bronchial epithelial cells dictate downstream responses, despite being structural components of the airway wall and not inflammatory or immune cells.…”
Section: Bronchial Epitheliummentioning
confidence: 99%
“…Epithelial cells actively secrete immune mediators in response to environmental stimuli [61], which are different in patients with asthma compared with controls [62]. Asthmatic epithelium also has altered barrier function [63], and is a critical bridge between external environmental exposures and pulmonary inflammatory and immune responses [64]. Bronchial epithelial cells dictate downstream responses, despite being structural components of the airway wall and not inflammatory or immune cells.…”
Section: Bronchial Epitheliummentioning
confidence: 99%
“…It is known that nitric oxide, prostaglandin E2 and Toll-like receptor 5 regulate CXCL8 expression post-transcriptionally [38][39][40]. It is possible that these mechanisms are ERK1/2-and p38 MAPK-dependent [41]. Pre-stimulation with IFN-γ significantly decreased CCL26 expression and generally increased IL-6 and CXCL8 expression (except for CXCL8 in bronchial cells) after IL-4 or IL-13 stimulation in the nasal, bronchial and small airway epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…TEER represents a marker of redifferentiation of the epithelial cells across the cell culture. There are some data from adults [43][44][45][46] showing lower TEER in asthmatic epithelial cultures, but fewer data are available in children. One study, using cultures derived from bronchial brushings, found no significant difference in TEER between asthmatic and non-asthmatic children hemokine gene expression ans laeoinflammatory transcription factors (NF-kB, AP-1 and STAT1/2) chemokine gene expression ans lae [36].…”
Section: Bronchial Epithelium In Childrenmentioning
confidence: 99%